Święty Maksymilian Maria Kolbe – męczeństwo z miłości - Wiesław Bar (Polonia Sacra)
Post St. Maximilian Kolbe – the martyrdom of love, was developed in three parts. In the first part, on based of 26th texts from the Scriptures and the 33rd texts from the Conference, presents a concept of love by Father Maximilian as God’s gift to man, as revealed in Jesus crucified, who left himself in the Eucharist, that the man is strengthened in the love of neighbor, also enemies, even to give one’s life. The modest texts in the number about martyrdom, reveal just the habitual readiness of Knight of the Immaculate, as evidenced by the intention of the Mass of April 30, 1918, celebrated the day after his ordination: “pro gratia et martyrii apostolate, pro me et confratribus in Collegio”. The second part contained reflections on the death qualification of Fr Maximilian, paying attention to verify the legal and canonical elements of martyrdom. The third part shows the consequences – social and for jurisprudence of the Congregation for the Causes of Saints – to declar Fr Maximilian as martyr. Includes, among others, arguments of a group of senators, with which initiative was declared the Year 2011 as “Year of St. Maximilian Kolbe”.